EFFECTS OF ORGANIZATION SIZE ON ACCOUNTS RECEIVABLES MANAGEMENT IN THE HOTEL INDUSTRY IN KENYA - Ngugi, Simon K.; Gakure, Prof. Roselyn W.; Gekara, Dr. Geoffrey M; kahiri, Dr. James K. (American Journal of Accounting, 2017)
Purpose: The purpose of the study was to establish the effects of organization size on accounts receivables management in the hotel industry in Kenya Methodology: The target population of the study was 47 hotels and lodges in Kenya. A sample of 141 respondents was selected using stratified random sampling in each hotel and lodge to group respondents into three strata. The strata were that of top management, finance staff and credit control staff. This study used both primary and secondary data. Data collection methods used included: questionnaires and secondary data collection guide. Secondary data was collected for all variables for a period of three years (2007 to 2010). Data was analyzed quantitatively and presented descriptively and illustrated by use of tables and charts. Information was sorted, coded and input into the statistical package for social sciences (SPSS) for production of graphs, tables, descriptive statistics and inferential statistics. In particular, means, standard deviations, and frequencies. Inferential statistics such as factor analysis and odd ratio regression were also used. Results: Based on the findings, the study concluded that size of the organization had a positive effect on accounts receivables management in the hotel industry in Kenya. It can be concluded that the larger the hotel the higher the accounts receivables to be managed hence the need to have a strong management structures and policies in place. The study concludes that size of the organization is statistically significant in explaining accounts receivables in the hotel industry in Kenya. Unique contribution to theory, practice and policy: Based on the findings, the study recommends that hotel management should ensure that there are standardized and written manuals with the policies regarding trade credit and its management.